Addressing Socioeconomic Disparities in Developing Student-Centred Learning Environments (Universitas Pendidikan Indonesia Kampus Cibiru, 2023)
This theoretical study explores the crucial problem of overcoming socioeconomic inequalities in education while promoting student-centred learning settings. Socioeconomic disparities in education refer to the unequal distribution of resources and opportunities based on socioeconomic status which presents substantial difficulties for students from poor backgrounds. To reduce these inequities and improve educational outcomes, the paper highlights the significance of student-centred learning environments that give individual needs and involvement priority. To overcome socioeconomic gaps, the article examines a variety of approaches, such as policy interventions, culturally competent instruction and parent-community involvement. Drawing on case studies and best practices, the paper provides successful initiatives and cutting-edge strategies that have successfully closed the gap between underprivileged and privileged listeners. The report emphasizes the need of tackling socioeconomic gaps in education, not just for academic accomplishment but also for the advancement of social justice and equity. In conclusion, addressing socioeconomic disparities in education and developing student-centred learning environments is crucial for promoting educational equity and improving outcomes for students from disadvantaged backgrounds should be a top priority by educators and other stakeholders.